Prevalence of dry eye syndrome associated to face mask among Tabanan General Hospital Health workers in 2021 - Rania Ayu Permata Putri Kornia; I Putu Rustama Putra; Ni Wayan Sedani; Cynthia Dewi M (DiscoverSys Inc., 2021)
Background: The continuous development of COVID-19 has made face masks became a mandatory part of our daily routine, but there has been an increase in dry eye syndrome (DES) from the regular used of face masks. Health workers who are obliged to use face masks are the one that has risk factors for experiencing DES, including health workers at Tabanan General Hospital, as one of the COVID-19 referral hospitals in Bali. The purpose of this study was to calculate the prevalence of DES associated to face masks and characteristics of DES among Tabanan General Hospital health workers in 2021. Methods: This research was a descriptive cross sectional study that conducted at Tabanan General Hospital from March to April 202. The sample was 64 health workers at Tabanan General Hospital with consecutive sampling techniques using the Ocular Surface Disease Index (OSDI) questionnaire. Data were collected by using questionnaire. Data were annalyse descriptively by using SPSS 25 and the result were provide in table. Results: The prevalence of DES associated to face masks among Tabanan General Hospital health workers in 2021 was 70.3%, with a prevalence of mild degrees 15.6%, moderate 12.5%, and severe 42.2%. The prevalence of surgical mask users was greater than Filtering Face Piece (FFP) 2 mask users in mild and severe degrees of DES. Characteristics of DES among Tabanan General Hospital health workers in 2021 were found mostly in age 30-39 years old, more in females, without DM history, non-smokers, and without eye surgery history. Conclusion: Most of the health workers at Tabanan General Hospital experiencing DES associated to face masks, and mostly with a severe degree. Among those with DES, there were more surgical mask users than FFP2 mask users. Future studies are needed to analyze the association between DES and face masks.